Modelling, Analysis and Control of Nonlinear Discrete and Continuous Mechanical Structures Dedicated for Mechatronic Applications - Awrejcewicz, Jan; Grzelczyk, Dariusz (Discontinuity, Nonlinearity, and Complexity, 2026)
This is the Special Issue dedicated to the 13th International Conference on "Dynamical Systems - Theory and Applications" (DSTA-2015) which was held on December 7-10, 2015 in Łódź Poland. The main aim of the conference was to provide a platform for researchers and engineers to present and discuss the current state and contemporary investigations in different disciplines of science, bioscience, and engineering. This issue presents eight selected manuscripts related to the modeling, analysis and control of nonlinear discrete and continuous mechanical structures met in mechatronic applications.